Optimization of Bread Production and Sales with Simulation and Data Mining - Muhammad Takdir Muslihi; Faruq Ratuhaji (Nusantara Science and Technology Proceedings, 2022)
The bread production process and sales strategy are two things that determine the success of sales in a bakery. Evaluation of production systems and changing sales strategies at the bakery can increase sales value. This research aims to implement simulation and data mining on bread's production and sales process at a predetermined location. With this method, we can change the business strategy as needed without having to waste a lot of time and money. As a result of the simulation, we found that the third scenario succeeded in speeding up the bread production time by 4 times. Rounding, Inspection, Baking, and Packaging utilities are 0.43, 0.67, 0.34, and 0.46, respectively. As a result of data mining, we found that more than 33% of those who buy cakes (pastry) also buy bread. this can be a reference for changing sales strategy. The novelty of this study is that it combines two methods of analyzing business processes, namely simulation, and data mining.